Information needs, goals and problems : research and evaluation of the research on users of school libraries - Lasić-Lazić, Jadranka (Array, 1997)
This work considers information as an important strategic source for fulfilling social and individual need for informative education and it treats a library as the particular possibility of getting such education. There, one can learn how to use various sources of information. The researching that is, in direct or indirect way, treating the problem of informative education in the library is studied and critically analysed. The relation between user and librarian, as an important authority for information and education, is stressed as well as the role of the librarian who knows the needs the users may have. The validity of research is analysed pointing to the mistakes that could have been avoided. The objective of the research has been to point out the mistakes and methodological weaknesses so that they could be avoided in the future research.